2019
DOI: 10.3389/fpls.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

Cold Induced Antisense Transcription of FLOWERING LOCUS C in Distant Grasses

Abstract: Functional conservation of RNAs between different species is a key argument for their importance. While few long non-coding RNAs are conserved at the sequence level, many long non-coding RNAs have been identified that only share a position relative to other genes. It remains largely unknown whether and how these lncRNAs are conserved beyond their position. In Arabidopsis thaliana, the lncRNA COOLAIR is transcribed antisense from FLOWERING LOCUS C (FLC) in response to cold. Despite relatively low sequence simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…COOLAIR is involved in FLC repression by both autonomous and vernalization pathways, which leads to flowering in spring. Homology-based search was performed to find FLC locus and antisense FLC transcripts in other monocots, and the results showed that although there is no sequence conservation between antisense FLC transcripts and Arabidopsis COOLAIR lncRNA, the locations of these transcripts were conserved in six grass species including T. aestivum (Jiao et al, 2019). COLDAIR was identified as another lncRNA potentially regulating FLC expression.…”
Section: Developmental Stage-related Lncrnasmentioning
confidence: 99%
“…COOLAIR is involved in FLC repression by both autonomous and vernalization pathways, which leads to flowering in spring. Homology-based search was performed to find FLC locus and antisense FLC transcripts in other monocots, and the results showed that although there is no sequence conservation between antisense FLC transcripts and Arabidopsis COOLAIR lncRNA, the locations of these transcripts were conserved in six grass species including T. aestivum (Jiao et al, 2019). COLDAIR was identified as another lncRNA potentially regulating FLC expression.…”
Section: Developmental Stage-related Lncrnasmentioning
confidence: 99%
“…Brachypodium has also been shown to encode lncRNAs, similar to COOLAIR , which target FLC -like genes for downregulation during vernalization ( Jiao et al, 2019 ). Two high confidence lncRNAs were detected for BdOS2 , while one lncRNA could be detected for BdOS1 .…”
Section: Evidence For Conserved Function: What Do We Already Know?mentioning
confidence: 99%
“…Expression of these lncRNAs is induced by vernalization, and their induction is significantly higher in a winter accession compared to a facultative accession, while their expression is absent in a spring accession. Knockdown of BdCOOLAIR2 via RNAi also affects the rate of silencing of BdOS2 in BdTR3C, though it is not essential for the complete silencing of BdOS2 ( Jiao et al, 2019 ). This information suggests that lncRNAs complement the mechanisms which silence FLC -like genes in grasses, in a similar fashion to FLC regulation in Arabidopsis , although this mode of regulation is accession dependent.…”
Section: Evidence For Conserved Function: What Do We Already Know?mentioning
confidence: 99%
“…Histone acetylation is important in the FCA-mediated thermal adaptation of developing seedlings, chlorophyll biosynthesis, and seedling photosynthetic fitness [ 56 ]. The FLC/FCA module functions not only in hot conditions, but also in cold, providing adaptation to winter conditions through an FLC antisense transcript COOLAIR [ 53 , 57 ]. This may explain why BRL3ox plants demonstrated high gene expression not only in the category “Response to Water Deprivation”, but also in the categories “Response to Temperature Stimulus” and “Cold Acclimation” [ 2 ].…”
Section: The Priming Phenomenonmentioning
confidence: 99%